Effects of oral administration or feeding of sodium citrate or acetate to pigs on post-mortem glycolysis, pH decline, and pork quality attributes - J W Stephens; Michael E Dikeman; John A Unruh; M D Haub; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 2005)
Previous studies have shown that citrate has the potential to inhibit phosphofructokinase (PFK), a key enzyme in post-mortem glycolysis. The objective of our study was to determine the effects of oral administration and feeding of citrate or acetate to pigs on post-mortem glycolysis, pH, and pork quality attributes. In Experiment 1, citrate, acetate, or water was orally administered to 30 pigs 45 min before stunning (electric plus captive bolt). In Experiment 2, citrate or acetate was fed to 30 gilts in 454 g of feed 60 min before stunning. Ante-mortem treatment had no effect (P>0.05) on muscle pH or post mortem concentrations of glycolytic metabolites: glucose- 6 phosphate, fructose-6 phosphate, fructose-1,6 bisphosphate, glyceraldehyde-3 phosphate, dihydroxyacetone phosphate, or lactate. Minor, but inconsistent, differences in quality attributes were found in longissimus chops and inside and outside semimembranosus quality attributes among treatments (P>0.05). The reason for the lack of PFK inhibition is not known. Glycolytic-metabolite data indicate that PFK was a main regulatory enzyme in post-mortem muscle.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Pork; pH; Glycolysis; Citrate; Acetate; Swine